Description of the Characteristics of People with HIV/AIDS at Caritas Weetebula Hospital, Southwest Sumba District 2021 - Seingo, Tineke Jumiati; Manurung, Imelda F; Toy, Sarci M. (Faculty of Public Health, Nusa Cendana University, 2024)
The Southwest Sumba District Health Office noted that 27 HIV cases and 17 AIDS cases were recorded in 2018 with a total of 44 people. In 2019, the number of cases decreased slightly, 21 HIV cases and 21 AIDS cases with a total of 42 people. This study aims to describe the knowledge characteristics and self-stigma of PLHIV (People Living with HIV/AIDS) at Karitas Weetebula Hospital, Southwest Sumba Regency, in 2021. This quantitative descriptive research with a cross-sectional approach was conducted from February to March 2022, involving 42 PLHIV as samples selected through total sampling. The results showed that most respondents had good knowledge about HIV/AIDS (73.8%) and the majority were employed as civil servants, entrepreneurs, or laborers (61.9%). Self-stigma among respondents was relatively low; however, social participation (59.6%) and community acceptance of PLHIV (54.8%) remained low. This study recommends enhancing HIV/AIDS health education, particularly in rural communities, to reduce stigma and discrimination against PLHIV